School-Based Health Centers in an Era of Health Care Reform: Building on History - Keeton, Victoria (2012)
School-based health centers (SBHCs) provide a variety of health care services to youth in a convenient and accessible environment. Over the past 40 years, the growth of SBHCs evolved from various public health needs to the development of a specific collaborative model of care that is sensitive to the unique needs of children and youth, as well as to vulnerable populations facing significant barriers to access. The SBHC model of health care comprises of on-school site health care delivery by an interdisciplinary team of health professionals, which can include primary care and mental health clinicians. Research has demonstrated the SBHCs’ impacts on delivering preventive care, such as immunizations; managing chronic illnesses, such as asthma, obesity, and mental health conditions; providing reproductive health services for adolescents; and even improving youths’ academic performance. Although evaluation of the SBHC model of care has been complicated, results have thus far demonstrated increased access to care, improved health and education outcomes, and high levels of satisfaction. Despite their proven success, SBHCs have consistently faced challenges in securing adequate funding for operations and developing effective financial systems for billing and reimbursement. Implementation of health care reform (The Patient Protection and Affordable Care Act [P.L. 111-148]) will profoundly affect the health care access and outcomes of children and youth, particularly vulnerable populations. The inclusion of funding for SBHCs in this legislation is momentous, as there continues to be increased demand and limited funding for affordable services. To better understand how this model of care has and could further help promote the health of our nation’s youth, a review is presented of the history and growth of SBHCs and the literature demonstrating their impacts. It may not be feasible for SBHCs to be established in every school campus in the country. However, the lessons learned from the synergy of the health and school settings have major implications for the delivery of care for all providers concerned with improving the health and well-being of children and adolescents.